2013
DOI: 10.1074/jbc.m112.441451
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into DNA Recognition by Zinc Fingers Revealed by Structural Analysis of the Oncoprotein ZNF217

Abstract: Background: Classical zinc finger proteins are extremely abundant and interact with DNA using a well defined recognition code. Results: We solved the structure of ZNF217 bound to its cognate DNA. Conclusion: ZNF217 presents a unique DNA interaction pattern including a new type of protein-DNA contact. Significance: This study deepens our understanding of DNA recognition by classical zinc fingers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 75 publications
3
40
0
Order By: Relevance
“…If these distinct binding events induce shift changes that are relatively uncorrelated, the overall observed changes will be small. Consistent with this idea, we recently observed substantially smaller chemical shift changes when the ZF protein ZNF217 bound to a non-specific DNA target than when it bound a sequence for which it had specificity (50). This explanation would also partially account for our mutagenesis data, which indicate that the contribution of individual residues to overall affinity is small, perhaps due to the existence of a number of binding modes.…”
Section: Discussionmentioning
confidence: 56%
“…If these distinct binding events induce shift changes that are relatively uncorrelated, the overall observed changes will be small. Consistent with this idea, we recently observed substantially smaller chemical shift changes when the ZF protein ZNF217 bound to a non-specific DNA target than when it bound a sequence for which it had specificity (50). This explanation would also partially account for our mutagenesis data, which indicate that the contribution of individual residues to overall affinity is small, perhaps due to the existence of a number of binding modes.…”
Section: Discussionmentioning
confidence: 56%
“…(De et al, 2014-this issue) show that, although the chemical shift changes observed for ETV6-ETS are overall in the same direction for both specific and non-specific complexes, the magnitude of the changes is significantly smaller for the latter complex. We noted a similar pattern in our analysis of the DNA-binding properties of the zinc-finger protein ZNF217 [10] and the spectra shown in the study of the HoxD9 homeodomain [18] appear to tell a similar story. In each case, the authors report that the protein is N 90% saturated with DNA, which means that the smaller chemical shift changes do not arise from incomplete complex formation.…”
supporting
confidence: 59%
“…However, a picture is beginning to emerge that the overall geometry of DNA recognition is conserved between cognate and non-cognate interactions. An NMR structure of the lac repressor (LacI) DBD (DNA-binding domain) bound to nonspecific DNA [9] and NMR studies of both homeodomain [7] and zinc-finger domains [10,11] show that the canonical DNA-binding surface is used in nonspecific interactions.…”
mentioning
confidence: 99%
“…S5). Comparable patterns of relative NMR spectral changes have been reported for the HMG-box 26 and ZNF217 zinc finger 27 proteins bound to non-specific versus specific DNA oligonucleotides. This is not a trivial result of incomplete saturation of the ETV6 D446 –DNA nonsp complex, as the protein was ~ 98 % bound (Supplemental Fig.…”
Section: Etv6 Binds Non-specific Dna Via the Canonical Ets Domain Intmentioning
confidence: 86%